Experimental investigation and theoretical prediction of sleeve reinforced PGFRP composite under flexural loading for cross-arm application - Vijayvignesh Namasivayam Sukumaar; Mohamad Ridzwan Ishak; Mohd Na'Im Abdullah; Mohamed Yusoff Mohd Zuhri; Muhammad Asyraf Muhammad Rizal (Results in Engineering)
Pultruded glass fibre reinforced polymer composite is used as a cross-arm material in high-rise transmission tower application to suspend insulators, conductor cables and vibration dampeners. Due to long-term static loading conditions, they fail due to incompetency in the cross-arm's mechanical properties. This study establishes a feasible method to improve the service life by retrofitting a sleeve reinforcement, sandwiching the composite fastened by bolting, to strengthen the overall structure. This study is focused, at the coupon scale level, to determine the influence of this structural element upon the elastic mechanical properties under instantaneous and creep load conditions. The composite material and the stainless steel sleeve are fabricated using waterjet machining and laser cutting respectively. A comparative study among the virgin and varying lengths of sleeve reinforced composite is established for homogenizing this concept at the actual scale applications. It has been observed that the composite reinforced with the sleeve of 100% length as that of the composite specimen showed enhancement in its flexural elastic moduli by about 178% and 138% under instantaneous and creep load conditions as compared to its virgin counterpart. The Findley numerical model in compliance with creep results was used to generate equations to predict the deterioration of mechanical properties. This data helps to determine the functional service life of the composite in actual application. The sleeve installation has been found to increase the bending strength thereby resulting in reduced strain and promoting localized encapsulation, resilience, toughness, load transfer capability and creep strain resistance of the PGFRP composite.